Producing Refuse Derived Fuel with Refining Industry Oily Sludge and Mushroom Substrates - Chien Li Lee; Chih-Ju G. Jou (Energies, 2022)
The sludge in this study was obtained from refinery crude oil storage tanks. It contained a high proportion of hydrocarbon composition and harmful substances (such as polycyclic aromatic hydrocarbons and benzene). Through the microwave irradiation treatment process, the harmful substances were removed from the sludge which was then recycled and combined with agricultural waste mushroom substrates to produce refuse derived fuel (RDF). The results showed that the calorific value of RDF was 7279 cal/g when the blending ratio (wt/wt) of oil sludge and mushroom substrates was 5:5. On the other hand, when the portion of the mushroom substrates was increased, the sludge became easier to ignite with better combustion reaction. When the blending ratio (wt/wt) was changed from 8:2 to 5:5, the ignition index and comprehensive performance index were increased by 51.9 and 50.2%. Therefore, mixing the sludge with agricultural waste mushroom substrates is in line with the concept of waste recycling and circular economy.